Multi-label classification using error correcting output codes - Kajdanowicz, Tomasz; Kazienko, Przemysław (Zielona Góra: Uniwersytet Zielonogórski)
A framework for multi-label classification extended by Error Correcting Output Codes (ECOCs) is introduced and empirically examined in the article. The solution assumes the base multi-label classifiers to be a noisy channel and applies ECOCs in order to recover the classification errors made by individual classifiers.
Keywords: machine learning; supervised learning; multi-label classification; error-correcting output codes; ECOC; ensemble methods; binary relevance; framework